Gambaran Tekanan Darah dan Hemoglobin Pasien Gagal Ginjal Yang Menjalani Terapi Hemodialisis - Endrat Kartiko Utomo; Erna Rochmawati (Jurnal Keperawatan Duta Medika, 2021)
Introduction: Hypertension and anemia are included in the focus of care in chronic renal failure patientsundergoing hemodialysis. This is because the incidence of hypertension and anemia can aggravate kidneydisease and can cause difficulties in kidney patients undergoing hemodialysis.Objectives: This study aims to determine the blood pressure and hemoglobin levels of patients with chronickidney failure undergoing hemodialysis therapy.Methods: This research is a descriptive study, with a total sample of 48 patients using a side probabilitytechnique with a purposive sampling type and with inclusion criteria: patients aged 18-65 years, male andfemale, patients undergoing hemodialysis therapy for more than 3 months, the patient received hemodialysistherapy twice a week, and the patient was willing to be a respondent.Results: The mean blood pressure of chronic renal failure patients undergoing hemodialysis therapy was 162.5mmHg (systolic) and 88.5 mmHg (diastolic). Meanwhile, the average hemoglobin level of patients with chronicrenal failure undergoing hemodialysis therapy was 10 g/dl.Conclusions: The blood pressure of patients with chronic renal failure was categorized as hypertension and thepatient's hemoglobin level was still normal. With the results of this study, it is hoped that it will become areference or reference for health workers and researchers in formulating interventions for patients in thefuture